New aspects of vitamin C during prenatal development - Čapo, Ivan; Popović, Milan; Čapo, Nataša; Stilinović, Nebojša; Sekulić, Slobodan (Biologia Serbica, 2021)
Vitamin deficiency leads to a cascade of reactions that ultimately result in the development of disease. Vitamin C is synthesized from glucose in the liver of most mammals, with the exception of humans, non-human primates and guinea pigs (Cavia porcelus). Namely, because of the evolutionary loss of the gene for the synthesis of L-gulonolactone oxidase (Gulo gene), endogenous synthesis of vitamin C is no longer possible, and these mammals must consume vitamin C to survive. Vitamin C is directly involved in collagen synthesis and severe deficiencies result in scurvy, a postnatal form of this vitamin deficiency. Although the consequences of postnatal vitamin C deficiency are relatively clear, there is still insufficient data concerning the effects of vitamin C deficiency during the prenatal period. Recent data indicate the importance of collagen in basal membrane integrity and its possible disturbance during vitamin C depletion. We have developed a novel guinea pig model of prenatal pial basal membrane disturbance during prenatal deprivation of Vitamin C. Results indicate that disturbance of collagen synthesis induces breaches in the pial basement membrane. As a consequence, the Bergman glia connection is lost, and neuron migration disturbances occur with developing dysplasia of cerebellar cortex, which can be found in Lissencephaly type II. The fact that neither humans nor guinea pigs can synthesize vitamin C creates an opportunity for further research into the impact of prenatal deprivation of vitamin C in developing neuron migration disorders.